A High Potential Polyanion Cathode Material for Rechargeable Mg‐Ion Batteries. Issue 8 (10th June 2022) - Li, Cuicui; Lin, Lu; Wu, Wanlong; Sun, Xiaoqi
Abstract: The development of Mg‐ion batteries is hindered by the lack of cathode materials that allow facile and reversible Mg 2+ intercalation at high potential. Herein, the authors present a polyanion cathode material of K2 (VO)2 (HPO4 )2 (C2 O4 )⋅4.5H2 O (KVPCH) for Mg‐ion batteries. The inductive effect of polyanions ensures the high redox potential of the vanadium centers. In addition, the material contains structural water located between the layers. It helps with Mg 2+ desolvation at the electrode–electrolyte interface and facilitates its diffusion in the structure, as confirmed by experimental analysis and theoretical calculations. Thanks to those factors, the KVPCH electrode presents excellent Mg storage capability at room temperature. It delivers 121 mAh g –1 capacity at 1C with a high average discharge potential of 0.16 V versus Ag/Ag + (3.2 V vs Mg/Mg 2+ ). A capacity retention of 87% is realized after 1500 cycles at 5C. A rocking‐chair Mg‐ion full cell is also demonstrated with the KVPCH cathode and a MoOx anode, which achieves 46 mAh g –1 capacity (based on the total active material mass of two electrodes). This work would bring effective paths for the design of cathode materials for Mg‐ion batteries. Abstract : A layer polyanion cathode material K2 (VO)2 (HPO4 )2 (C2 O4 )⋅4.5H2 O is revealed for Mg‐ion batteries. A high discharge potential of 0.16 V versus Ag/Ag +, corresponding to 3.2 V versus Mg/Mg 2+ is achieved thanks to the inductive effect. The structural water helps with Mg 2+ desolvation at the electrode/electrolyte interface and facilitates Mg 2+ diffusion inside the lattice.